Redefining Higher Education Quality Assurance in Southern Africa through the Infusion of Artificial Intelligence - Chikuvadze Pinias; Mhishi Misheck; Dziva Daimond; Makuvire Claretah; Chikerema Teresa; Machona Liberty (Quality Assurance Practices for Transformative Higher Education in Southern Africa, 2025)
The infusion of Artificial Intelligence (AI) into various spheres of life, including education for sustainable development, has revolutionised key pillars of higher education such as teaching, community service, research, innovation, and industrialisation. This chapter focuses on redefining quality assurance (QA) in Southern Africa’s (Angola, Botswana, Eswatini (Swaziland), Lesotho, Malawi, Mozambique, Namibia, South Africa, Zambia, and Zimbabwe) higher education by embedding AI into its systems. It emphasises the importance of conceptualising AI within the framework of QA processes in higher education. Central to this chapter is an exploration of the transformative impact of AI on curriculum development in higher education. Thus, AI is revolutionising QA by introducing innovative methods and tools such as AI-Powered Test Automation, predictive analytics, root cause analysis, security and compliance, etc., that enhance efficiency, accuracy, and adaptability. The chapter further investigates how AI enhances compliance and quality checks in educational institutions. Ethical considerations tied to the use of AI in QA processes are also critically analysed. By contributing to ongoing debates and discussions, this chapter reinforces the growing necessity of integrating AI into higher education systems, with particular attention to QA.